Effects of Flavonoid-rich Plant Extracts on In vitro Ruminal Methanogenesis, Microbial Populations and Fermentation Characteristics - Kim, Eun T. (Asian-Australas J Anim Sci, 2015)
The objective of this study was to evaluate the in vitro effects of flavonoid-rich plant extracts (PE) on ruminal fermentation characteristics and methane emission by studying their effectiveness for methanogenesis in the rumen. A fistulated Holstein cow was used as a donor of rumen fluid. The PE (Punica granatum, Betula schmidtii, Ginkgo biloba, Camellia japonica, and Cudrania tricuspidata) known to have high concentrations of flavonoid were added to an in vitro fermentation incubated with rumen fluid. Total gas production and microbial growth with all PE was higher than that of the control at 24 h incubation, while the methane emission was significantly lower (p<0.05) than that of the control. The decrease in methane accumulation relative to the control was 47.6%, 39.6%, 46.7%, 47.9%, and 48.8% for Punica, Betula, Ginkgo, Camellia, and Cudrania treatments, respectively. Ciliate populations were reduced by more than 60% in flavonoid-rich PE treatments. The Fibrobacter succinogenes diversity in all added flavonoid-rich PE was shown to increase, while the Ruminoccocus albus and R. flavefaciens populations in all PE decreased as compared with the control. In particular, the F. succinogenes community with the addition of Birch extract increased to a greater extent than that of others. In conclusion, the results of this study showed that flavonoid-rich PE decreased ruminal methane emission without adversely affecting ruminal fermentation characteristics in vitro in 24 h incubation time, suggesting that the flavonoid-rich PE have potential possibility as bio-active regulator for ruminants.